Trends in the Antiviral Chemical Activity of Material Surfaces Associated With the SARS-CoV-2 Outbreak - Schio, Aline Lucchesi; Michels, Alexandre Fassini; Fongaro, Gislaine; Figueroa, Carlos Alejandro (Frontiers in Chemical Engineering, 2021)
The novel coronavirus designated as SARS-CoV-2 has risen the first pandemic caused by coronavirus and by November 26, 2020 is responsible for more than 1,410 million deaths. This scenario evidences that despite previous pandemics and epidemics in the world’s history, the current worldwide measures to contain and to mitigate viruses’ outbreaks are still disabled and insufficient. Therefore, this perspective reinforces the need for new and practical approaches for antiviral material developments and presents current technologies and its advances in this field of research focusing especially in surface materials since it is one of the most common interaction pathways. Furthermore, the roll that nanotechnology has been playing in the combat of viruses as well as the mechanisms that science has been discovering to inactivate these pathogenic microorganisms is presented. Finally, we suggest introducing new legislation and norms rather more specified on virucidal agents (materials and devices) than bactericidal ones in human environments such as hospitals, nursing homes, buses, and shopping centers to mitigate the current and future virus-based pandemics and epidemics.